Pesquisa de Equus caballus papillomavirus-2 em carcinomas de células escamosas e papilomas genitais de equinos machos no Rio Grande do Sul, Brasil - Silva, Tanara Raquel de Oliveira da (2022)
Squamous cell carcinoma (SCC) is a malignant neoplasm arising from keratinocytes. It is highly prevalent in horses, often affecting the penis and prepuce. Its benign counterpart, the papilloma, is also common in the genital region, and can be induced by infection with papillomaviruses (PVs). Although it is known that equine genital papillomas may have a viral origin, the etiology of genital SCCs is not fully understood. The presence of a new PV, Equus caballus papillomavirus type 2 (EcPV-2), was recently detected among genital SCCs in male horses. Based on this, it is believed that there may be an association between EcPV-2 infection and the genesis of some equine genital papillomas and SCCs. Since its discovery in 2010, EcPV-2 has been described in different countries in North America and Europe, however, with no reports in Brazil. The objective of this research is to investigate the presence of EcPV-2 within genital papillomas and SCCs of male Brazilian horses. We investigated 40 SCCs and papillomas involving the penis and/or prepuce, diagnosed in the biopsy or necropsy routine of the Laboratório de Patologia Veterinária (LPV), Universidade Federal de Santa Maria (UFSM), and in the biopsy routine of the Setor de Patologia Veterinária (SPV), Universidade Federal do Rio Grande do Sul (UFRGS) (2000-2021). Data related to breed and age were taken from the histopathological reports. The paraffin blocks were recovered for the preparation of Hematoxylin and Eosin slides, immunohistochemistry (IHC) for PV (40/40) and polymerase chain reaction (PCR) using a pair of primers specific for PV (23/40) and another pair specific for EcPV-2 (40/40). Positive cases were sequenced. Of the included cases, 34 were invasive SCCs, three were carcinomas in situ (CIS), and three were papillomas. The median age was 13.2 years, and of the horses with informed reproductive status, three were stallions and two were geldings. The breed Crioula was the most represented (16/40). All tumors showed varying degrees of lymphoplasmacytic inflammation, with two SCC's showing lymphatic vascular invasion and two showing blood invasion. Within the carcinomas, or in the tumor-adjacent mucosa, swollen, degenerated keratinocytes with a weakly basophilic cytoplasm, occasionally containing a clear vacuole and a large nucleus, were ocasionally observed. Viral inclusions were absent in all cases. In the IHC using anti-BPV-1 antibody, four cases (two SCCs, one CIS and one papilloma) had positive immunostaining, observed in the nucleus of neoplastic keratinocytes (CIS and papilloma) or in the epithelium adjacent to the tumor (SCCs). PCR revealed seven positive cases for PV and five of these positive for EcPV-2. Three EcPV2-positive cases and two PV-positive and EcPV2-negative were sequenced, and compatible with EcPV-2. With this study, we can confirm the presence of EcPV-2 in Brazilian horses. We hope this study stimulates further research related to this new virus, ultimately contributing to a better understanding of transmission routes, and to the development of effective preventive measures.